Trend in the incidence of hepatitis A in mainland China from 2004 to 2017: a joinpoint regression analysis - Yuan-Sheng Li; Bei-Bei Zhang; Xi Zhang; Song Fan; Li-Ping Fei; Chao Yang; Ning-Jun Ren; Xiang Li; Ya-Mei Luo; Jun-Hui Zhang (BMC Infectious Diseases, 2022)
Abstract Background China has experienced a continuous decreasing trend in the incidence of hepatitis A in recent years. Temporal trend analyses are helpful in exploring the reasons for the changing trend. Thus, this study aims to analyse the incidence trend of viral hepatitis A by region and age group in mainland China from 2004 to 2017 to evaluate the effectiveness of prevention and control measures. Methods Data on hepatitis A and population information were collected and analysed with a joinpoint regression model. Annual percentage changes (APCs) and average annual percentage changes (AAPCs) were estimated for the whole country and for each region and age group. Results From 2004 to 2017, the seasonality and periodicity of hepatitis A case numbers were obvious before 2008 but gradually diminished from 2008 to 2011 and disappeared from 2012–2017. The national incidence of hepatitis A (AAPC =  − 12.1%) and the incidence rates for regions and age groups showed decreasing trends, with differences in the joinpoints and segments. Regarding regions, the hepatitis A incidence in the western region was always the highest among all regions, while a nonsignificant rebound was observed in the northeastern region from 2011 to 2017 (APC = 14.2%). Regarding age groups, the hepatitis A incidence showed the fastest decrease among children (AAPC =  − 15.3%) and the slowest decrease among elderly individuals (AAPC =  − 6.6%). Among all segments, the hepatitis A incidence among children had the largest APC value in 2007–2017, at − 20.4%. Conclusion The national annual incidence of hepatitis A continually declined from 2004 to 2017 and the gaps in hepatitis A incidence rates across different regions and age groups were greatly narrowed. Comprehensive hepatitis A prevention and control strategies, including the use of routine vaccination during childhood in mainland China, especially the implementation of the national Expanded Program on Immunization (EPI) in 2008, resulted in substantial progress from 2004 to 2017. However, gaps remain. Regular monitoring and analysis of hepatitis A epidemic data and prompt adjustment of hepatitis A prevention and control strategies focusing on children, elderly individuals and those living in certain regions are recommended.